Composite urinary biomarkers to predict pathological tubulointerstitial lesions in lupus nephritis. (October 2018) - Ding, Y; Nie, L-M; Pang, Y; Wu, W-J; Tan, Y; Yu, F; Zhao, M-H
Objective: This study aimed to evaluate the clinical value of urinary biomarkers including kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL), and monocyte chemoattractant protein-1 (MCP-1) in lupus nephritis. Methods: A total of 109 biopsy-proven lupus nephritis patients were included and 50 healthy individuals were used as normal controls. Urinary KIM-1, NGAL, and MCP-1 levels were measured by ELISA and their correlations with clinical and histological features were assessed. Receiver operating characteristic curves were performed and the Cox regression model was applied to identify prognostic factors associated with renal outcomes. Results: Active lupus nephritis patients exhibited elevated urinary levels of KIM-1, NGAL, and MCP-1 compared with lupus nephritis patients in remission ( P  < 0.001) and normal controls ( P  < 0.001). The urinary KIM-1 level was correlated with pathological tubular atrophy ( r  = 0.208, P  < 0.05) and increased significantly in the presence of interstitial inflammatory lesions ( P  = 0.031). Urinary KIM-1, NGAL, and MCP-1 levels were higher in patients with active tubulointerstitial lesions than in those with only chronic lesions ( P  = 0.015, P  = 0.230, and P  = 0.086, respectively). A combination of KIM-1, NGAL, and MCP-1 was a good indicator for diagnosing active tubulointerstitial lesions (area under the curve: 0.796). The combination of KIM-1 and NGAL was identified as an independent risk factor for renal outcomes (hazard ratio = 7.491, P  < 0.05). Conclusion: Urinary KIM-1, NGAL, and MCP-1 levels were associated with kidney injury indices in lupus nephritis. The combination of the three biomarkers showed increased power in predicting tubulointerstitial lesions and renal outcomes.